KOMUNIKASI PERSUASIF FOLLOWERS AKUN @Pandemictalks USIA 18-24 TAHUN DI INSTAGRAM DALAM PEMBENTUKAN SIKAP POSITIF SELAMA PANDEMI COVID-19 - Alifa Khairunissa Adelia (2022)
The Covid-19 pandemic as we all know is a relatively new experienced by the world community. Indonesia is said to be one of the many countries that have also experienced the Covid-19 pandemic, this situation has been going on for quite a while. The situation that has occurred as a result of this pandemic has resulted in many changes through many aspects of life, especially in the way people communicate and seek information to be in the spotlight in the face of change because one of the main needs of the Indonesian people today is accuracy. information and data regarding the development of the Covid-19 pandemic. One of the social media platforms that discusses the development, information and education of the Covid-19 pandemic is from Instagram @pandemictalks. Through this understanding, this study was written to determine the effectiveness of positive attitude changes that occur in followers of the Instagram account @pandemictalks aged 18-24 years while following an Instagram account. The research method used is descriptive qualitative using the theory of Elaboration Likelihood Model. The results of the research obtained are that active followers of the @pandemictalks account are individuals who prioritize and carry out their obligations to carry out vaccines. Then, have a positive attitude in disseminating information and invite many parties to comply with health protocols. Then there is another positive attitude, namely complying with the 5M process and finally self-discipline when following this account, making a positive attitude more calm and alert when exposed to Covid-19 because the information packaged in the @pandemictalks account is packaged interactively and easily. understandable and not monotonous.